NON-TRADITIONAL LABOR RELATIONS: IN FOREIGN EXPERIENCE - Antonella Lopopolo; Khakberdiev Aziz Komiljonovich (Scholar Express Journals, 2023)
The thesis questions argument that extending labor contracts to part-time, seasonal and temporary workers facilitate to diminish the rate informal employment in developing countries. In fact, the formal employment relies on many aspects of labor law; however, one of key components is the labor contract allowing individuals become workers. Therefore, this study looks for the most optimal types of labor contracts that can ease the process of formal employment. The research brings the practice of Uzbekistan and Italy on nontraditional contracts for workers. The research demonstrates current situation of labor law in Uzbekistan and comparative analyses between Uzbek labor law and Italian’s labor law regarding part-time and temporary contracts. However, this research reveals that introduction of new types of labor contracts is not sufficient to enhance the whole situation of informal employment in Uzbek labor market. Overall, the hypothesis of this research demonstrates that flexible labor relationships through labor contracting which can promote transformation from informal to formal job creation and stimulate individuals to enter into the formal labor market in a consequence ensuring respect for labor rights of atypical workers.
Keywords: atypical workers; non-regular workers; part-time contract; informal employment in Central Asia